A) 3(x+3)=2(x+4)+x+1=
b) 4(3x+2)+5(2x+3)=(2x+13)=
c) 4(x-2)-2(x-4)5(x+1)-3x=
d) 2(x-4)=2(2x-1)+6(x+1)=
e) 0,2x+0,3=1,3
f) 0,2x+0,3=1,3
g) 0,83x+0,82=0,23x+1,52=
h) 0,6x+2(0,1x-0,1)=0,2(x+1)=
i) 0,15(2x+4)=2(1,3+0,3x)-0,6=
j) 0,1(x+1)-0,05(3x-10)=0,4-0,35x

Wszystkim z góry dziekuje!!!

2

Odpowiedzi

2010-02-26T18:11:20+01:00
A)
3(x+3)=2(x+4)+x+1
3x + 9 = 2x + 8 + x + 1
3x - 2x - x = 8 + 1 - 9
0x = 0

b)
4(3x+2)+5(2x+3)=(2x+13)
12x + 8 + 10x + 15 = 2x + 13
12x + 10x - 2x = 13 -8 - 15
20x = -10 / :20
x = -0,5

c)
4(x-2)-2(x-4) = 5(x+1)-3x
4x - 8 - 2x + 8 = 5x + 5 - 3x
4x - 2x - 5x + 3x = 5 + 8 - 8
0x = 5

d)
2(x-4)=2(2x-1)+6(x+1)
2x - 8 = 4x - 2 + 6x + 6
2x - 4x - 6x = -2 + 6 + 8
-8x = 12 / : -8
x = -1,5

e)
0,2x+0,3=1,3
0,2x = 1,3 - 0,3
0,2x = 1 / : 0,2
x = 5

f)
0,2x+0,3=1,3
0,2x = 1,3 - 0,3
0,2x = 1 / : 0,2
x = 5

g)
0,83x+0,82=0,23x+1,52
0,83x - 0,23x = 1,52 - 0,82
0,6x = 0,7 / : 0,6
x = 1,17 [1,1(6)]

h)
0,6x+2(0,1x-0,1)=0,2(x+1)
0,6x + 0,2x - 0,2 = 0,2x + 0,2
0,6x + 0,2x - 0,2x = 0,2 - 0,2
0,6x = 0

i)
0,15(2x+4)=2(1,3+0,3x)-0,6
0,3x + 0,6 = 2,6 + 0,6x - 0,6
0,3x - 0,6x = 2,6 - 0,6 - 0,6
-0,3x = 1,4 / : -0,3
x = -0,7 [-0,(6)]

j)
0,1(x+1)-0,05(3x-10)=0,4-0,35x
0,1x + 0,1 - 0,15x + 0,5 = 0,4 - 0,35x
0,1x - 0,15x + 0,35x = 0,4 - 0,1 - 0,5
0,3x = -0,2 / : 0,3
x = -0,7 [-0,(6)]
1 1 1
2010-02-26T23:49:03+01:00
A)
3(x+3)=2(x+4)+x+1
3x+9=2x+8+x+1
3x-2x-x=8+1-9
0=0

b)
4(3x+2)+5(2x+3)=(2x+13)
12x+8+10x+15=2x+13
12x+10x-2x=13-8-15
20x=-10
x=-0,5

c)
4(x-2)-2(x-4)=5(x+1)-3x
4x-8-2x+8=5x+5-3x
4x-2x-5x+3x=5+8-8
0≠5

d)
2(x-4)=2(2x-1)+6(x+1)
2x-8=4x-2+6x+6
2x-4x-6x=-2+6+8
-8x=12
x=-1,5

e)
0,2x+0,3=1,3
0,2x=1,3-0,3
0,2x=1
x=5

f)
0,83x+0,82=0,23x+1,52
0,83x-0,23x=1,52-0,82
0,6x=0,7
x=1⅙

g)
0,6x+2(0,1x-0,1)=0,2(x+1)
0,6x+0,2x-0,2=0,2x+0,2
0,6x+0,2x-0,2x=0,2+0,2
0,6x=0,4
x=⅔

h)
0,15(2x+4)=2(1,3+0,3x)-0,6
0,3x+0,6=2,6+0,6x-0,6
0,3x-0,6x=2,6-0,6-0,6
-0,3x=1,4
x=-4⅔

i)
0,1(x+1)-0,05(3x-10)=0,4-0,35x
0,1x+0,1-0,15x+0,5=0,4-0,35x
0,1x-0,15x+0,35x=0,4-0,1-0,5
0,3x=-0,2
x=-⅔
1 2 1